100 years of iodine testing of the cervix: A critical review and implications for the future. (June 2021) - Reich, Olaf; Pickel, Hellmuth
Abstract: Objectives: We aim to describe the history of iodine testing of the cervix and identify areas where further work is required. Study design: We conducted a search of PubMed and Google Scholar. Full article texts were reviewed. Reference lists were screened for additional articles and books. 37 basic articles in journals including ones written in German and three basic articles in books were identified. Results: Glycogen staining of the ectocervical squamous epithelium with iodine goes back to Paul Ehrlich (1854–1915). Walter Schiller (1887–1960) examined nearly 200 different dyes and found that vital staining of the cervical squamous epithelium was best achieved with Lugol's iodine solution, which was indicated by Jean Guillaume Lugol (1786–1851) for disinfection of the vagina. In 1928 W. Lahm observed that the glycogen content of a squamous epithelium cell decreases as anaplasia increases. From the outset, H. Hinselmann included the iodine test in the minimum requirements for colposcopy. In 1946 H. J. Wespi first mentioned the finding of an " uncharacteristic iodine negative area ." The first international colposcopic terminology from Graz in 1975 lists the " iodine light area " among the different colposcopy findings. The IFCPC nomenclatures from Rome 1990, Barcelona 2002, and Rio de Janeiro 2011 have evaluated the iodine test and classified their findings differently. A breakthrough to effective cervical cancer screening in resource-limited settings in Africa, India, and Latin America was achieved with R. Sankaranarayanan's publication on naked-eye visual inspection of the cervix after application of Lugol's iodine. Conclusions: This paper is a step toward a better understanding of what we think and do today with iodine testing and what problems and upcoming tasks will arise in future.